1989
DOI: 10.1007/bf00812068
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties of isolated transverse tubular membranes

Abstract: This review addresses the major biochemical and structural characteristics of isolated transverse tubule (T-tubule) membranes, including methods of isolation and morphology of purified membranes, evaluation of attendant membrane activities, including ion pumps and channels, and structural and compositional analyses of functionally relevant components. Particular emphasis is placed on the Mg2+-ATPase, its localization in the T-system, its unusual kinetic properties, its possible functions, and its potential reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 191 publications
4
42
0
Order By: Relevance
“…One possible effect of detergents is the dissociation of protein oligomers. The proposal that the oligomeric state of the ecto-ATPase affects its enzymatic activity was made previously (33,34). To answer the question about the relationship of the transmembrane domains to the oligomeric state of the protein and its sensitivity to detergents, we made variants of the ectoapyrase with one or no transmembrane domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible effect of detergents is the dissociation of protein oligomers. The proposal that the oligomeric state of the ecto-ATPase affects its enzymatic activity was made previously (33,34). To answer the question about the relationship of the transmembrane domains to the oligomeric state of the protein and its sensitivity to detergents, we made variants of the ectoapyrase with one or no transmembrane domains.…”
Section: Resultsmentioning
confidence: 99%
“…Second, sucrose density gradient sedimentation profiles of both the expressed ectoapyrase in COS-7 cells and the native ectoapyrases from LG2 cells (data not shown) are identical: ectoapyrase behaved as a tetramer after solubilization with digitonin, a detergent that has little effect on the enzymatic activity, and became monomeric after solubilization with Triton X-100, a detergent that inhibits the activity. It has been suggested that detergents may inactivate ectoapyrase by destabilizing an oligomeric state of the protein (33,34), and it has been reported that chicken gizzard muscle ecto-ATPase (34) and rat lung ectoapyrase (39) are disulfide-linked homotrimers and homodimers, respectively. However, this work is the first demonstration that the ectoapyrase is a noncovalent tetramer.…”
Section: Fig 4 Expression Of Wild Type and Mutant Ectoapyrases In Cmentioning
confidence: 99%
“…Diabetes-induced hyperlipidemia and the alterations in membrane phospholipids and fatty acids have been shown to depress membrane-bound enzyme activity (Kuwahara et al, 1997 (Sabbadini & Dahms, 1989). Thus, the pumps are essential for the regulation of cell volume, uptake of nutrients, and cell growth and differentiation, and are also critical for normal functioning of excitable and non-excitable tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Because T-tubule membranes are particularly enriched in cholesterol [3] and it has been reported that the oxidation of membrane cholesterol increases membrane fluidity [19], we studied the effects of cholesterol oxidase treatment on ecto-ATPase activity. Figure 4 shows a complete loss of enzymic activity after a 30 min treatment of chicken T-tubules with cholesterol oxidase.…”
Section: Figure 4 Effect Of Treatment With Cholesterol Oxidase On Ectmentioning
confidence: 99%
“…In skeletal muscle, a very efficient E-type ATPase activity, first designated as Mg# + -ATPase or ' basic '-ATPase, is associated with transverse tubule (T-tubule) membranes [3]. This activity was extensively characterized in rabbit and chicken skeletal muscle T-tubule vesicles [4][5][6].…”
Section: Introductionmentioning
confidence: 99%